Degree of impact of factors that affect the start-up of small and medium enterprises in Singapore. - Huang, Eunice Yifang. (2008)
This report aims to uncover the factors that affect the start-up of SMEs in Singapore and the degree of their impact. This includes finding out in detail each of the following factors: Government, Education, Economic Conditions, Legal Environment, Technology, Infrastructure and Financial, and how they affect the start-up of SMEs in Singapore.